Efektivitas Instagram “Earth Hour Bogor” sebagai Media Kampanye Lingkungan - Ghina Shabrina Ulfa; Anna Fatchiya (Institut Pertanian Bogor, 2018)
Social media is a new media that has more interactive communication than conventional media. Earth Hour Bogor is a social movement that utilizes social media instagram as their campaign media. The purpose of this research is the effectiveness analysis of Instagram @ ambogor as media campaign of social movement of environment and the factors that influence it. The methods of the research are quantitative and supported with qualitative data. The results of the social media show Instagram @ehbogor effective in stimulating the attention of followers, causing interest to know more, the desire to participate, and follow the campaign activities organized and invite others. Factors that influence this are the location of the residence and the frequency of the campaign information presented at the Attention stage. At the interest level is the type of work, the frequency of respondents in accessing Instagram and clarity of campaign information. At the stage of desire did not find the variables that affect, while the action stage is the location of residence and motivation of respondents in access Instagram.